Dealing with financial crises: How much help from research? - Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Has economic research been helpful in dealing with the financial crises of the early 2000s? On the whole, the answer is negative, although there are bright spots. Economists have largely failed to predict both crises, largely because most of them were not analytically equipped to understand them, in spite of their recurrence in the last 25 years. In the pre-crisis period, however, there have been important exceptions - theoretical and empirical strands of research that largely laid out the basis for our current thinking about financial crises. Since 2008, a flurry of new studies offered several different interpretations of the US crisis: to some extent, they point to potentially complementary factors, but disagree on their relative importance, and therefore on policy recommendations. Research on the euro debt crisis has so far been much more limited: even Europe-based researchers - including CEPR ones - have often directed their attention more to the US crisis than to that occurring on their doorstep. In terms of impact on policy and regulatory reform, the record is uneven. On the one hand, the swift and massive liquidity provision by central banks in the wake of both crises is, at least partly, to be credited to previous research on the role of central banks as lenders of last resort in crises and on the real effects of bank lending and monetary policy. On the other hand, economists have had limited impact on the reform of prudential and security market regulation. In part, this is due to their neglect of important regulatory choices, which policy-makers are therefore left to take without the guidance of academic research-based analysis.
urn:nbn:de:hebis:30:3-351230
Keywords: G01; G18; G21; G28; H81; O16; 330; financial crisis; risk taking; systemic risk; financial regulation; monetary policy; politics